Investigating the dynamic nature of L2 willingness to communicate. (June 2015) - Pawlak, Mirosław; Mystkowska-Wiertelak, Anna
Abstract: The complex nature of willingness to communicate (WTC) in a second language (L2) manifests itself in its diverse conceptualizations, ranging from a personality trait to a context-related feature. The significance of the concept lies in the fact that it integrates psychological, linguistic, educational, and communicative dimensions of language that traditionally have been investigated separately. Recently, a dynamic character of WTC has been recognized and it has been shown that one's willingness to speak may fluctuate during one communicative event. The study reported in this paper aimed to investigate changes in learners' willingness to speak in the course of a conversation about upbringing, performed in pairs, and to identify factors responsible for such changes. The participants were 8 Polish majors enrolled in a three-year Bachelor of Arts program and the data were collected by means of self-ratings, questionnaires and interviews. The analysis showed that the participants' WTC was indeed in a state of flux, being influenced by such variables as the topic, planning time, cooperation and familiarity with the interlocutor, the opportunity to express one's ideas, the mastery of requisite lexis, the presence of the researcher, and a host of individual variables.